Latest Advancement in the Management of Xerostomia: A Review - Venetia Aranha (JCDR Research and Publications Private Limited, 2021)
Xerostomia, also known as dry mouth, is a subjective sensation arising due to the reduced salivary flow. The dry mouth interferes with normal oral functions such as swallowing, chewing and speech. An increase in the incidence of dental caries and oral infections that may impact the oral health is also seen. The aetiology of dry mouth may be due to systemic diseases, drugs or by radiation to the head and neck, the causes hence being multifactorial. The prevalence of dry mouth is commonly seen in nearly half of the elderly population and one fifth of the younger individuals. Salivary substitutes are used to manage xerostomia. However, for longstanding xerostomia, a lot of potential systemic therapies exist. Oral health care providers are now making significant contributions to the diagnosis and are aware of the latest trends in the management of xerostomia. This review aimed to illustrate the current trends in the management of xerostomia.